Preconcentration of Some Trace Elements in Natural Waters as Their 8-Hydroxy Quinoline Chelates Using Amberlite XAD-4 Resin - GHORBANI, AZAM; RABBANI, MOHAMMAD; AFLAKI PASHAKI, FRAIDUN; ROOZBAHANI, ALI (Asian Journal of Chemistry, 2010)
In this paper we have developed a simple and reliable method for the determination of Fe, Ni, As, Sn, Co and Mn ions in natural water samples by inductively coupled plasma optical emission spectrometry (ICP-OES), using solid phase extraction. The procedure is based on the retention of analytes in the form of 8-hydroxyquinoline (8-HQ) complexes on a mini column of XAD-4 resin and subsequent elution with nitric acid. The influence of various analytical parameters including the amount of solid phase, pH, elution factors (concentration and volume of eluting solution), volume of sample solution and amount of ligand on the extraction efficiency of analytes was investigated. The average relative standard deviations of the determinations were below 7 %. The limit of detection (3S, n = 12) for analytes were found in the range of 0.02-1.2 μg L-1. The method was applied to the analysis of trace elements in some natural waters.